2018
DOI: 10.17116/jnevro20181183189-93
|View full text |Cite
|
Sign up to set email alerts
|

A study on the association of genes for pro-inflammatory cytokines and depression

Abstract: The IL-1B С-511T and TNF-a G-308A polymorphisms were associated with depression; CC genotype (р=0,001, OR=1.9 CI 1,3-2,7) and GG genotype (р=0,001, OR=3,0 CI 1,8-4,9) were the risk factors. The results suggest that immune factors may play a role in the development of depression. The authors highlight the role of clinical polymorphism of depression that makes it difficult to form homogenous groups of patients and to select phenotypes for biological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Serum CRP levels were related to decreased motivation and psychomotor retardation [82], as well as to symptoms of anxiety in psychiatric patients [83,84]. Even some polymorphisms of pro-inflammatory cytokine genes, including IL-1β, TNF, and CRP, appeared to be linked with depression and treatment response [85][86][87][88].…”
Section: Peripheral Inflammation and Depressionmentioning
confidence: 99%
“…Serum CRP levels were related to decreased motivation and psychomotor retardation [82], as well as to symptoms of anxiety in psychiatric patients [83,84]. Even some polymorphisms of pro-inflammatory cytokine genes, including IL-1β, TNF, and CRP, appeared to be linked with depression and treatment response [85][86][87][88].…”
Section: Peripheral Inflammation and Depressionmentioning
confidence: 99%
“…The −511C allele in IL1B was associated with higher ILB expression [30] and higher IL-1β levels. The −511C/T polymorphism was associated with a depression [31,34]. The risk variant for depression was the CC genotype (p = 0.001, OR = 1.9 CI 1.3-2.7) [31].…”
Section: Santos Et Al (2016) [50]mentioning
confidence: 94%
“…The −511C/T polymorphism was associated with a depression [31,34]. The risk variant for depression was the CC genotype (p = 0.001, OR = 1.9 CI 1.3-2.7) [31]. There is much research dedicated to studying the contribution of IL1B-511C/T in the pathogenesis of depression disorders.…”
Section: Santos Et Al (2016) [50]mentioning
confidence: 99%
“…Several genes are associated with anxiety [ 38 ], including the interleukin (IL)-1β gene [ 39 ]. An Italian study reported the role of the IL-1β gene in developing anxiety and the effects of psychobiotics in reducing anxiety symptoms, with 43.24% of anxious subjects being A allele carriers of the IL-1β gene and the rest 11.43% of subjects being anxious non-carriers.…”
Section: Reviewmentioning
confidence: 99%